Antimicrobial activity of the extract, fractions and punicalagin from the rind of the fruit of Punica granatum against clinical isolates from cows with mastitis (Research, Society and Development, 2021)
The aim of this study was to evaluate the antimicrobial activity of the extract, fractions and purified punicalagin from peel pomegranate fruit of the granada and wonderful varieties against Coagulase Positive Staphylococcus (CPS) and Coagulase- negative Staphylococcus (CNS), isolated from cows with mastitis. The pomegranate pods were dried in an oven, ground and the ethanol extract was prepared by maceration and percolation. The fractions were obtained by liquid-liquid fractionation, and the purification of punicalagin was carried out in a chromatographic column filled with Diaion® HP-20. HPLC and NMR (1H and 13C -Acetone-d6) were used for identification, quantification and structural elucidation of punicalagin and MIC (CLSI-M7A10) were determined for 23 clinical isolates. The punicalagin content was higher in the extract and fractions of the granada variety, reaching 81.5% in the purified punicalagin sample, which showed good antimicrobial activity against clinical isolates, with emphasis on S. aureus and S. schleiferi schleiferi, where the MIC was 31.75 µg/ml. Thus. punicalagin was defined as an important metabolite for the antimicrobial potential of P. granatum fruits, however, the synergism of metabolites of ethyl acetate fractions and aqueous fraction of the granada variety, had considerable importance for the good antimicrobial activity of these fractions, compared to 100 % of the CPS and CNS. Thus, the results obtained confirm the antimicrobial activity of the metabolites present in the pomegranate peel, which may support new research on pharmaceutical formulations based on P. granatum, as an alternative for the treatment, prevention and control of mastitis.